2013
DOI: 10.1111/ejn.12274
|View full text |Cite
|
Sign up to set email alerts
|

Reduced brain corticotropin‐releasing factor receptor activation is required for adequate maternal care and maternal aggression in lactating rats

Abstract: The brain corticotropin-releasing factor (CRF) system triggers a variety of neuroendocrine and behavioural responses to stress. Whether maternal behaviour and emotionality in lactation are modulated by CRF has rarely been investigated. In the present study, we measured CRF mRNA expression within the parvocellular part of the paraventricular nucleus in virgin and lactating Wistar rats bred for high (HAB) and low (LAB) anxiety-related behaviour or non-selected for anxiety (NAB). Further, we intracerebroventricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 56 publications
4
49
2
Order By: Relevance
“…Recently, we have demonstrated that hypo-activation of CRF-R centrally (Klampfl et al, 2013) as well as in the medial-posterior BNST (mpBNST) or the anterior-dorsal BNST (adBNST) is essential for the adequate expression of maternal behavior and for the hypo-anxious state in lactating rats. Activation of CRF-R2 in the mpBNST and of CRF-R1 in the adBNST results in a strong reduction of maternal behavior while both receptor subtypes concomitantly mediate maternal anxiety in the mpBNST, but not the adBNST.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have demonstrated that hypo-activation of CRF-R centrally (Klampfl et al, 2013) as well as in the medial-posterior BNST (mpBNST) or the anterior-dorsal BNST (adBNST) is essential for the adequate expression of maternal behavior and for the hypo-anxious state in lactating rats. Activation of CRF-R2 in the mpBNST and of CRF-R1 in the adBNST results in a strong reduction of maternal behavior while both receptor subtypes concomitantly mediate maternal anxiety in the mpBNST, but not the adBNST.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…For experiment 1 -3, pregnant females were also single-housed after surgery to guarantee recovery and undisturbed delivery (Klampfl et al, 2013). On the day of birth, litters were culled to eight pups of mixed sexes.…”
Section: Animalsmentioning
confidence: 99%
“…This is associated with elevated levels of Crh mRNA in the pPVN under basal conditions. It is not known whether prenatal social stress affects CRH expression in other regions of the brain; however, as the activation of the central CRH system is known to impair maternal behaviour (Pedersen et al 1991, Gammie et al 2004, Klampfl et al 2013, this may contribute to reduced mother-pup interactions and reduced nursing.…”
Section: Maternal Behaviour In Rodentsmentioning
confidence: 99%
“…These results are consistent with previous studies showing that high-licking dams are less neophobic than low-licking dams (Francis, Champagne, and Meaney, 2000) and that, more generally, postpartum rats display less anxiety-related behavior than nulliparous females (reviewed in Lonstein, 2007). This lower "trait-level of emotional reactivity observed in the more maternally responsive females may be what allows them to be more accepting of and attentive to pups, and may be regulated by differences in their central GABA, oxytocin, and corticotropin releasing hormone receptor signaling (Walker et al, 2001;Klampfl et al, 2013;Hansen, Ferreira, and Selart, 1985;Lonstein, Maguire, Meinlschmidt, and Neumann, 2014).…”
mentioning
confidence: 99%